Pengaruh Penggunaan Teknik Membaca Cepat Pada Mata Pelajaran Bahasa Indonesia Kelas VII MTs NW Teros Tahun Pelajaran 2018/2019 - Fathurrahman, Fathurrahman (FAKULTAS TARBIYAH, 2020)
This study aims to determine the increasing effect of using speed reading techniques on Indonesian subjects on class VII MTs NW Teros in the 2018/2019 academic year. This research was conducted in MTs. NW Teros, Teros Village, Labuhan Haji District, East Lombok. This study uses a quantitative approach. The population of this study was 49 students of class VII. Data collection techniques were carried out through test and observation methods. Data analysis was carried out by statistical t-test (t-test). The results showed that from the calculation results above, it turns out that the